A influência no outro: das escritas do eu ao suicídio de Werther - Santos, Roberson Rosa dos (2011)
The starting point for this text is an interest in the self narratives addressed to another that take place in psychotherapeutic environments. Reading the book "The Sorrows of Young Werther" by Goethe, it becomes clear that this form of self expression, communicating one s innermost and most obscure feelings, was a feature exploited by the Sturm und Drang movement, and soon afterwards by the German Romantics too. Following this logic, we move to a psychoanalytical and sociological reading of suicide, seeking to better understand the different facets of this act, proposed by Goethe as a solution to passions misunderstood by eighteenth century German bourgeois society. Next, we approach the concept of self presented by Fichte as the basis for investigations into the relations between the self and its other. Here we trace the influence of the other on suicide, on Werther s letters and also in the constitution of the I through the "Mirror stage as a formative function of the self", by Jacques Lacan. From this we use Antonio Candido s studies to problematize Werther, Goethe and his public as characters in a game of mirrors. Werther's letters are an expression of his innermost being, and need confirmation, a response, from the other. This influence of and from the other is present in various contexts.